Cumulative blood pressure from early adulthood to middle age is associated with left atrial remodelling and subclinical dysfunction assessed by three-dimensional echocardiography: a prospective post hoc analysis from the coronary artery risk development in young adults study. (29th June 2018) - Vasconcellos, Henrique D; Moreira, Henrique T; Ciuffo, Luisa; Nwabuo, Chike C; Yared, Guilherme S; Ambale-Venkatesh, Bharath; Armstrong, Anderson C; Kishi, Satoru; Reis, Jared P; Liu, Kiang; Lloyd-Jones, Donald M; Colangelo, Laura A; et al.
Abstract: Aims: To evaluate the association of cumulative blood pressure (BP) from young adulthood to middle age with left atrial (LA) structure/function as assessed by three-dimensional echocardiography (3DE) in a large longitudinal bi-racial population study. Methods and results: We conducted a prospective post hoc analysis of individuals enrolled at the Coronary Artery Risk Development in Young Adults, which is a multi-centre bi-racial cohort with 30 years of follow-up. Cumulative systolic and diastolic BP levels were defined by summing the product of average millimetres of mercury and the years between each two consecutive clinic visits over 30 years of follow-up. Multivariable linear regression analyses were used to assess the relationship between cumulative systolic and diastolic BP with 3DE LA structure and function, adjusting for demographics and traditional cardiovascular risk factors. A total of 1033 participants were included, mean age was 55.4 ± 3.5 years, 55.2% women, 43.9% blacks. Cumulative systolic BP had stronger correlations than cumulative diastolic BP. Higher cumulative systolic BP was independently associated with higher 3D LA volumes: maximum ( β  = 1.74, P  = 0.004), pre-atrial contraction ( β  = 1.87, P  < 0.001), minimum ( β  = 0.76, P  = 0.04), total emptying ( β  = 0.98, P  = 0.006), active emptying ( β  = 1.12, P  < 0.001), and lower magnitude 3D LA early diastolic strain rate ( β  = 0.05, P  = 0.02). Higher cumulative diastolic BP was independently associated with higher 3D LA active emptying volume ( β  = 0.66, P  = 0.002), lower magnitude 3D LA early diastolic strain rate ( β  = 0.05, P  = 0.004), and higher magnitude 3D LA late diastolic strain rate ( β  = −0.04, P  = 0.05). Conclusion: Higher cumulative BP from early adulthood throughout middle age was associated with adverse LA remodelling evaluated by 3D echocardiography.